Pengembangan modul latihan pramuka penggalang di SDN 6 Porehu - Isyah Nurma Indah; Hisbullah Hisbullah; Lilis Suryani (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2026)
AbstractThis research is a development research that aims to determine the needs analysis, design, validity, practicality, and effectiveness of the Scout Penggalang training module based on Simulation Based Learning at SDN 6 Porehu, North Kolaka Regency. This learning model emphasizes direct learning experiences through simulation activities that resemble real conditions in scouting activities so that students can understand the material more concretely and directed. The type of research used is Research and Development with the ADDIE model which includes the stages of analyze, design, development, implementation, and evaluation. The research was conducted in 2025 involving 10 Scout Penggalang students as research subjects, while the object of the research was the Scout Penggalang training module. Data collection techniques were carried out through observation, interviews, questionnaires, and tests. The data obtained were analyzed qualitatively and quantitatively. The results of the needs analysis showed that Scout activities require systematic and contextual teaching materials to support students' practical skills. The developed module was validated by design experts, material experts, and language experts with a very valid category. The practicality test results showed a 95.2% response from instructors and 91% from students, categorized as very practical. The effectiveness test results showed an increase in student learning outcomes based on a comparison of pretest and posttest scores of 95.65%, categorized as highly effective, indicating that the module is suitable for use in Scouting learning activities at school.Keywords: Module, Scout Penggalang, Student Practical SkillsAbstrakPenelitian ini merupakan penelitian pengembangan yang bertujuan untuk mengetahui analisis kebutuhan, rancangan, validitas, kepraktisan, dan efektivitas modul latihan Pramuka Penggalang berbasis Simulation Based Learning di SDN 6 Porehu Kabupaten Kolaka Utara. Model pembelajaran ini menekankan pengalaman belajar langsung melalui kegiatan simulasi yang menyerupai kondisi nyata dalam aktivitas kepramukaan sehingga siswa dapat memahami materi secara lebih konkret dan terarah.Jenis penelitian yang digunakan adalah Research and Development dengan model ADDIE yang meliputi tahap analyze, design, development, implementation, dan evaluation. Penelitian dilaksanakan pada tahun 2025 dengan melibatkan 10 siswa Pramuka Penggalang sebagai subjek penelitian, sedangkan objek penelitian adalah modul latihan Pramuka Penggalang. Teknik pengumpulan data dilakukan melalui observasi, wawancara, angket, dan tes. Data yang diperoleh dianalisis secara kualitatif dan kuantitatif.Hasil analisis kebutuhan menunjukkan bahwa kegiatan Pramuka memerlukan bahan ajar yang sistematis dan kontekstual untuk mendukung keterampilan praktik siswa. Modul yang dikembangkan divalidasi oleh ahli desain, ahli materi, dan ahli bahasa dengan kategori sangat valid. Hasil uji kepraktisan menunjukkan respon pembina sebesar 95,2% dan respon siswa sebesar 91% dengan kategori sangat praktis. Hasil uji efektivitas menunjukkan peningkatan hasil belajar siswa berdasarkan perbandingan nilai pretest dan posttest sebesar 95,65% dengan kategori efektivitas tinggi sehingga modul layak digunakan dalam kegiatan pembelajaran Pramuka di sekolah. Kata Kunci: Modul, Pramuka Penggalang, Keterampilan Praktik Siswa